Promoting smoking cessation in Bangladeshi and Pakistani male adults: design of a pilot cluster randomised controlled trial of trained community smoking cessation workers. - Begh, R; Aveyard, P; Upton, P; Bhopal, R; White, M; Amos, A; Prescott, R; Bedi, R; Barton, P; Fletcher, M; Gill, P; Zaidi, Q; et al. (2009)
BACKGROUND: The prevalence of smoking is higher among Pakistani and Bangladeshi males than among the general population. Smokers who receive behavioural support and medication quadruple their chances of stopping smoking, but evidence suggests that these populations do not use National Health Service run stop smoking clinics as frequently as would be expected given their high prevalence of smoking. This study aims to tackle some of the main barriers to use of stop smoking services and adherence to treatment programmes by redesigning service delivery to be more acceptable to these adult male populations. The study compares the effectiveness of trained Pakistani and Bangladeshi smoking cessation workers operating in an outreach capacity ('clinic + outreach') with standard care ('clinic only') to improve access to and success of National Health Service smoking cessation services. METHODS/DESIGN: This is a pilot cluster randomised controlled trial based in Birmingham, UK. Super output areas of Birmingham will be identified in which more than 10% of the population are of Pakistani and/or Bangladeshi origin. From these areas, 'natural geographical communities' will be identified. Sixteen aggregated agglomerations of super output areas will be identified, separating areas from each other using buffer regions in order to reduce potential contamination. These natural communities will be randomised to 'clinic + outreach' (intervention) or 'clinic only' (control) arms. The use of stop smoking services and the numbers of people quitting smoking (defined as prolonged self-reported abstinence at four weeks, three months and six months) will be assessed in each area. In addition, we will assess the impact of the intervention on adherence to smoking cessation treatments and patient satisfaction.